Short Physical Performance Battery and Incident Cardiovascular Events Among Older Women. Issue 14 (21st July 2020) - Bellettiere, John; Lamonte, Michael J.; Unkart, Jonathan; Liles, Sandy; Laddu‐Patel, Deepika; Manson, JoAnn E.; Banack, Hailey; Seguin‐Fowler, Rebecca; Chavez, Paul; Tinker, Lesley F.; Wallace, Robert B.; LaCroix, Andrea Z.
Abstract : Background: The Short Physical Performance Battery (SPPB) is an inexpensive, reliable, and easy‐to‐implement measure of lower‐extremity physical function. Strong evidence links SPPB scores with all‐cause mortality, but little is known about its relationship with incident cardiovascular disease (CVD). Methods and Results: Women (n=5043, mean age=79±7) with no history of myocardial infarction or stroke completed 3 timed assessments—standing balance, strength (5 chair stands), and usual gait speed (4 m walk)—yielding an SPPB score from 0 (worst) to 12 (best). Women were followed for CVD events (myocardial infarction, stroke, or CVD death) up to 6 years. Hazard ratios were estimated for women with Very Low (0–3), Low (4–6), Moderate (7–9), and High (10–12) SPPB scores using Cox proportional hazard models adjusted for demographic, behavioral, and health‐related variables including objective measurements of physical activity, blood pressure, lipids, and glucose levels. Restricted cubic splines tested linearity of associations. With 361 CVD cases, crude incidence rates/1000 person‐years were 41.0, 24.3, 16.1, and 8.6 for Very Low, Low, Moderate, and High SPPB categories, respectively. Corresponding fully adjusted hazard ratios (95% CIs) were 2.28 (1.50–3.48), 1.70 (1.23–2.36) 1.49 (1.12–1.98), and 1.00 (referent); P ‐trend <0.001. The dose‐response relationship was linear (linear P <0.001; nonlinear P >0.38). Conclusions: Results suggest SPPB may provide a measure of cardiovascular health in older adults beyond that captured by traditional risk factors. Because of its high test‐retest reliability and low administrative burden, the SPPB should be a routine part of office‐based CVD risk assessment.